The role of rural producer organizations for agricultural service provision in fragile states - Ragasa, Catherine; Golan, Jennifer (International Food Policy Research Institute, 2012)
This paper assesses the role of rural institutions in the speedy recovery and growth of the agriculture and food sector in postconflict setting. This research was conducted to identify strategies and approaches to strengthen local institutions in the agricultural sector of the Democratic Republic of the Congo (DRC). Using a semi-structured interview approach with 181 rural producer organizations in three provinces of western DRC, this study finds varying types of rural producer organizations in the study areas and shows various internal and external factors affecting these organizations’ capacity to provide and facilitate agricultural services for their members. Greater interactions with other organizations, membership commitment through financial contributions, management capacity, and formal governance structures contribute to explaining these organizations’ performance in agricultural service delivery. Exogenous events were also found to affect organizational performance and service delivery outcomes. Organizations closer to areas with past conflict events face greater risks of conflict re-occurrence and experience limited agricultural and rural development programs, which reduce their ability to provide and facilitate agricultural services to their members. This result implies some evidence of negative relationship of conflict and collective action, in contrast to several studies that show a positive relation.